Common-pool resources are intrinsically unstable. Issue 2 (September 2017) - Saijo, Tatsuyoshi; Feng, Jun; Kobayashi, Yutaka
Efficient allocations in common-pool resources cannot be accomplished when appropriators are selfish. In addition, we find that a system of a common-pool resource is locally unstable if there are four or more appropriators. Such instability most likely makes efficiency worse than that in the Nash equilibrium. These results indicate that equilibrium analyses might not capture the essence of the common-pool resource problem. They may also provide an answer to the unexplained pulsing behavior among appropriators and inefficiency observed in experiments.